The antitumor effects of IFN-α are abrogated in a STAT1-deficient mouse - Lesinski, Gregory B. (American Society for Clinical Investigation, 2003)
IFN-α activates the signal transducer and activator of transcription (STAT) family of proteins; however, it is unknown whether IFN-α exerts its antitumor actions primarily through a direct effect on malignant cells or by stimulating the immune system. To investigate the contribution of STAT1 signaling within the tumor, we generated a STAT1-deficient melanoma cell line, AGS-1. We reconstituted STAT1 into AGS-1 cells by retroviral gene transfer. The resulting cell line (AGS-1(STAT1)) showed normal regulation of IFN-α–stimulated genes (e.g., H2k, ISG-54) as compared with AGS-1 cells infected with the empty vector (AGS-1(MSCV)). However, mice challenged with the AGS-1, AGS-1(STAT1), and AGS-1(MSCV) cell lines exhibited nearly identical survival in response to IFN-α treatment, indicating that restored STAT1 signaling within the tumor did not augment the antitumor activity of IFN-α. In contrast, STAT1(–/–) mice could not utilize exogenous IFN-α to inhibit the growth of STAT1(+/+) melanoma cells in either an intraperitoneal tumor model or in the adjuvant setting. The survival of tumor-bearing STAT1(–/–) mice was identical regardless of treatment (IFN-α or PBS). Additional cell depletion studies demonstrated that NK cells mediated the antitumor effects of IFN-α. Thus, STAT1-mediated gene regulation within immune effectors was necessary for mediating the antitumor effects of IFN-α in this experimental system.